Notes from underground - Dostoyevsky, Fyodor, 1821-1881 (Alfred A. Knopf, 1993)
A faithful translation of the classic written at the turn of the nineteenth to the twentieth century follows the narrator's withdrawal from his life as an official to the underground, where he makes passionate and obsessive observations on social utopianism and the irrational nature of humankind.